2018
DOI: 10.3233/jad-180627
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Music and Photograph Evoked Autobiographical Memories in People with Alzheimer’s Disease

Abstract: Background: Music evoked autobiographical memories (MEAMs) have been documented in people with Alzheimer's disease (AD), but it is unclear whether music is more effective than other familiar stimuli at evoking memories. Objective: To explore the frequency and specificity of memories in response to famous songs compared with photographs of famous events (photograph evoked autobiographical memories, PEAMs), and whether stimuli from the period of the reminiscence bump (10-30 years of age) were more likely to elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 38 publications
7
57
0
Order By: Relevance
“…Such memories are considered to be non-specific in the sense that they represent repeated or extended events that occurred during a particular time period, rather than a specific episode. This is consistent with earlier work suggesting MEAMs are less specific than PEAMs, and more likely to comprise semantic associations, lifetime periods or repeated/extended events, while PEAMs are more likely to relate to specific events, although this could be due to the nature of the photo stimuli (Baird et al, 2018(Baird et al, , 2020.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such memories are considered to be non-specific in the sense that they represent repeated or extended events that occurred during a particular time period, rather than a specific episode. This is consistent with earlier work suggesting MEAMs are less specific than PEAMs, and more likely to comprise semantic associations, lifetime periods or repeated/extended events, while PEAMs are more likely to relate to specific events, although this could be due to the nature of the photo stimuli (Baird et al, 2018(Baird et al, , 2020.…”
Section: Discussionsupporting
confidence: 91%
“…We found no group differences in the topic of memories evoked by music and photo stimuli at either time point. Overall, MEAMs were typically of a "period of life" (e.g., high-school years) consistent with prior research (Baird et al, 2018(Baird et al, , 2020see also Janata et al, 2007). Such memories are considered to be non-specific in the sense that they represent repeated or extended events that occurred during a particular time period, rather than a specific episode.…”
Section: Discussionsupporting
confidence: 84%
“…Lastly, music can prime or scaffold other (non-musical) functions. For example, music can stimulate autobiographical memory (e.g., Irish et al, 2006; Baird et al, 2018). It also engages the individual in new learning, exercise and cognitive training, and thus can reinforce the processes of ‘neural scaffolding.’ This is a process, originally defined by Park and Reuter-Lorenz (2009) in their ‘Scaffolding Theory of Aging and Cognition’ (STAC) model, which explains how life-course factors can enhance or deplete neural resources, influencing the developmental course of cognition and brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Receptive music-based treatments have been shown to significantly improve apathy (Massaia et al, 2018; Tang et al, 2018) and increase smiling behaviors compared to a control intervention of standard care (Raglio et al, 2008). Music also plays an important role in re-gaining access to emotions and memories, particularly in people with AD (e.g., El Haj et al, 2012; Baird et al, 2018). Interestingly, episodic memories evoked by music in people with AD tend to contain more emotional content and are more positively valanced, than episodic memories evoked in silence (El Haj et al, 2012; Cuddy et al, 2017), implying that the effects of music can benefit people with AD not only by eliciting memories, but also by inducing a positive state of mind.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, MEAMs have generated interest within clinical work, as some research has suggested that music can be an effective cue for autobiographical memories even in populations for which memory retrieval processes have become impaired due to disease or brain damage. For instance, music-in particular, self-selected music-has been shown to be a more effective cue for autobiographical memory recall than a silent control condition (El Haj, Postal, & Allain, 2012;Irish et al, 2006) and photographs of famous events (Baird et al, 2018) in people with Alzheimer's disease. This facilitation effect of music may be related to the more involuntary nature of retrieval of MEAMs, as involuntary retrieval may be relatively spared in comparison with deliberate recall processes in Alzheimer's disease (El Haj, Fasotti, & Allain, 2012).…”
mentioning
confidence: 99%